Pharmacoeconomic evaluation of ICS-LABA therapy in pediatric asthma: a cost-effectiveness and cost-utility analysis - Dai, Fan; Xu, Jin; Xu, Jing; Li, Wenjing (Frontiers in Pharmacology, 2025)
BackgroundAsthma is a chronic condition affecting children worldwide, with inhaled corticosteroid (ICS) and long-acting beta-agonist (LABA) combination therapies widely used in its management. However, the economic feasibility of these treatment regimens in pediatric asthma, particularly from a cost-effectiveness and cost-utility perspective, remains understudied. This retrospective study aimed to evaluate the clinical efficacy, cost-effectiveness, and cost-utility of multiple ICS-LABA therapy compared to single-inhaler therapy in children aged 0–18 years with asthma.MethodsA total of 59 pediatric patients diagnosed with asthma were included, divided into two main groups: the single-inhaler therapy group (Group A) and the multiple-inhaler regimens group (Group B). Group A consisted of subgroups A1 (salmeterol-fluticasone) and A2 (budesonide-formoterol), while Group B included subgroups B1 (two inhaled medications) and B2 (three inhaled medications). Clinical efficacy was measured based on symptom-free periods, while pharmacoeconomic analysis was conducted from the perspective of direct medical costs, including medication and non-medication costs. Both cost-effectiveness analysis (CEA) and cost-utility analysis (CUA) were employed, with outcomes presented as cost-effectiveness ratios (C/E), incremental cost-effectiveness ratios (ICER), and incremental cost-utility ratios (ICUR), using the willingness-to-pay (WTP) threshold of three times the per capita GDP of China.ResultsThe study found that while the total medication costs for multiple-inhaler regimens were higher than for single-inhaler therapies, the long-term cost-effectiveness and cost-utility favored multiple-inhaler regimens, especially triple regimens (Group B2) in complex and extended treatment scenarios. Shorter-term, less severe conditions were more economically manageable with single-agent therapies, with budesonide-formoterol (A2) showing superior cost-effectiveness over salmeterol-fluticasone (A1). Cost-effectiveness ratios (C/E) and incremental cost-effectiveness ratios (ICER) supported these findings. The cost-utility analysis, using QALYs, confirmed that multiple inhaler regimens were more cost-effective in children requiring prolonged treatment.ConclusionThis study provides important pharmacoeconomic insights into the treatment of pediatric asthma, highlighting the trade-offs between treatment costs and clinical outcomes. For children with more severe asthma, multiple ICS-LABA therapies, particularly triple therapy, offer better cost-effectiveness in the long term, while single-inhaler therapy remains economically viable for milder conditions. These findings support a stratified, individualized treatment approach and provide evidence for optimizing healthcare resource allocation in pediatric asthma management.